Development of an In Vitro Propagation Protocol and a Sequence Characterized Amplified Region (SCAR) Marker of Viola serpens Wall. ex Ging - Jha, Shipra Rani (Plants (Basel), 2020)
An efficient protocol of plant regeneration through indirect organogenesis in Viola serpens was developed in the present study. Culture of leaf explants on MS (Murashige and Skoog) medium supplemented with 2.0 mg/L 6-benzyladenine and 0.13 mg/L 2,4-dichloro phenoxy acetic acid. Adventitious shoot formation was observed when calli were transferred on to MS medium containing 0.5 mg/L α-naphthalene acetic acid and 2.25 mg/L kinetin, which showed the maximum 86% shoot regeneration frequency. The highest root frequency (80.92%) with the 5.6 roots per explant and 1.87 cm root length was observed on MS medium supplemented with 2 mg/L indole-3-butyric acid. The plantlets were transferred to the mixture of sand, coffee husk and soil in the ratio of 1:2:1 in a pot, and placed under 80% shade net for one month. It was then transferred to 30% shade net for another one month, prior to transplantation in the field. These plantlets successfully acclimatized under field conditions. A Sequence Characterized Amplified Region (SCAR) marker was also developed using a 1135 bp amplicon that was obtained from RAPD (Random Amplification of Polymorphic DNA) analysis of six accessions of V. serpens. Testing of several market samples of V. serpens using the SCAR marker revealed successful identification of the genuine samples of V. serpens. This study, therefore, provides a proficient in vitro propagation protocol of V. serpens using leaf explants and a SCAR marker for the authentic identification of V. serpens. This study will be helpful for conservation of authentic V. serpens.